2022
DOI: 10.1027/1866-5888/a000284
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellian Leader Effectiveness

Abstract: Abstract. Research on the effectiveness of Machiavellian leaders has found contradictory results. By linking socioanalytic and trait activation theory to the Machiavellianism and leadership literature, we argue that political skill may explain these findings by moderating the relation between Machiavellianism and leadership effectiveness. Using a multisource design and moderated mediation analyses with 153 leaders, 287 subordinates, and 153 superiors, we show that leaders who are both strongly politically skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
(108 reference statements)
0
19
0
1
Order By: Relevance
“…Pesquisas têm associado a habilidade política com outros atributos, como por exemplo, com o suporte organizacional (García-Chas, Neira-Fontela, Varela-Neira, & Curto-Rodríguez, 2019), a ética (Kacmar, Andrews, Harris, & Tepper, 2013), o desempenho do grupo (Lvina, Johns, & Vandenberghe, 2018), redução de comportamentos negativos no trabalho (De Clercq, Ul Haq, Azeem, & Ahmad, 2019), eficácia dos líderes (Genau, Blickle, Schütte, & Meurs, 2022), desempenho no trabalho (Blickle et al, 2011), (in)satisfação no trabalho (Hochwarter, James, Johnson, & Ferris, 2004;Atshan et al, 2022), venda orientada ao cliente (Good & Schwepker Jr, 2002), entre outros. Em tais pesquisas, observou-se que maior habilidade política tem efeitos em tais atributos.…”
Section: Estudos Correlatosunclassified
“…Pesquisas têm associado a habilidade política com outros atributos, como por exemplo, com o suporte organizacional (García-Chas, Neira-Fontela, Varela-Neira, & Curto-Rodríguez, 2019), a ética (Kacmar, Andrews, Harris, & Tepper, 2013), o desempenho do grupo (Lvina, Johns, & Vandenberghe, 2018), redução de comportamentos negativos no trabalho (De Clercq, Ul Haq, Azeem, & Ahmad, 2019), eficácia dos líderes (Genau, Blickle, Schütte, & Meurs, 2022), desempenho no trabalho (Blickle et al, 2011), (in)satisfação no trabalho (Hochwarter, James, Johnson, & Ferris, 2004;Atshan et al, 2022), venda orientada ao cliente (Good & Schwepker Jr, 2002), entre outros. Em tais pesquisas, observou-se que maior habilidade política tem efeitos em tais atributos.…”
Section: Estudos Correlatosunclassified
“…Research has associated political skill with other attributes, such as organizational support (García-Chas, Neira-Fontela, Varela-Neira, & Curto-Rodríguez, 2019), Ethics (Kacmar, Andrews, Harris, & Tepper, 2013),, the performance of the group (Lvina, Johns, & Vandenberghe, 2018),reduction of negative behavior at work (De Clercq, Ul Haq, Azeem, & Ahmad, 2019), Effectiveness of leaders (Genau, Blickle, Schütte, & Meurs, 2022), performance at work (Blickle et al, 2011), (in)Satisfaction at work (Hochwarter, James, Johnson, & Ferris, 2004;Atshan et al, 2022), customer-oriented sales (Good & Schwepker Jr, 2002), among others. In such research, it was observed that greater political ability has effects on such attributes.…”
Section: Related Studiesmentioning
confidence: 99%
“…In addition, the desire for control refers to the achievement and satisfaction of individuals by changing the world to meet their own needs (Yuan & Men, 2020). The Machiavellian leadership style affects members through a strong desire for control (Genau, Blickle, Schütte, & Meurs, 2022). Surveys have shown that the desire for control has a negative impact on openness (Zhang, 2020).…”
Section: The Desire For Control In Machiavellian Leadershipmentioning
confidence: 99%